Answer:
b=-a
Step-by-step explanation:
we know that b is located the same distance from 0 as another number, a, but in the opposite direction.
so the sum of the two numbers equal zero
a+b=0
a=-b or b=-a
Answer:
where i^2 = -1 (minus one)
So, i^2 = -1
i^4 = (i^2)^2 = (-1)^2 = -1 X-1 = 1
like ;
i^32 = (i^2)^16 = (-1)^16 = -1 X -1 X-1 X -1 X-1 X -1 X-1 X -1 X-1 X -1 X-1 X -1 X-1 X -1 X-1 X -1 X
= 1
Step-by-step explanation:
Hello,
You need to evaluate the equation, so:
3xˆ2+14x+8 --> 17xˆ2+8. Hop this helps!
~Brainliest
Answer:
(x + 3b)(3 + 5a)
Step-by-step explanation:
Assuming you require the expression factorised.
Given
3x + 9b + 5ax + 15ab ( factor the first/second and third/fourth terms )
= 3(x + 3b) + 5a(x + 3b) ← factor out (x + 3b) from each term
= (x + 3b)(3 + 5a) ← in factored form
C! All angles are the same